The Concept of Data Model Pattern Based on Fully Communication Oriented Information Modeling (FCO-IM) - Fazat Nur Azizah; Benhard Sitohang; Guido P. Bakema; Oerip S. Santoso (Journal of ICT Research and Applications, 2010)
Just as in many areas of software engineering, patterns have been used in  data modeling  to  create high quality  data  models.  We  provide  a  concept  of data  model  pattern  based  on  Fully  Communication  Oriented  Information Modeling  (FCO-IM),  a  fact  oriented  data  modeling  method.  A  data  model pattern is  defined  as  the relation  between  context, problem,  an d  solution.  This definition is adopted from the concept of pattern by Christopher Alexander. We define the concept of Information Grammar for Pattern (IG P) in the solution part of  a  pattern,  which  works  as  a  template  to  create  a  data  model.  The  IG P  also shows how a pattern can relate to other patterns. The data model pattern concept is then used to describe 15 data model patterns, organized into 4 categories. A case study on geographical location is provided to show the use of the concept in a real case.